SISTEM PENDUKUNG KEPUTUSAN PENENTUAN LOKASI PEMBANGUNAN PETERNAKAN AYAM MENGGUNAKAN METODE MOORA - Eka Larasati Amalia; Agung Nugroho Pramudhita; M Ridlwan Aditya (Antivirus : Jurnal Ilmiah Teknik Informatika, 2019)
This study aims to help beginner farmers to determine the location of the chicken farm construction using the MOORA method. The location factor for determining chicken farms is one of the important factors, because if the farm location is close to the highway, then the chicken will be exposed to transportation noise and easily stressed, but vice versa if the chicken farm is close to the cutting or sales location such as the market, the transportation costs will be relatively cheaper. The MOORA method has simple and stable mathematical calculations. MOORA method has the right mathematical calculation results in making a decision. The MOORA method has advantages over other methods, which are simpler and easier to implement. The level of selection in the MOORA method which is quite good can decide on an alternative solution in a problem.